2020
DOI: 10.1002/mnfr.202000788
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Tissue Multi‐Omics Nutrigenomics Indicates Context‐Specific Effects of Docosahexaenoic Acid on Rat Brain

Abstract: Scope: The influence of docosahexaenoic acid (DHA) on cardiometabolic and cognitive phenotypes, and multi-omic alterations in the brain under two metabolic conditions is explored to understand context-specific nutritional effects. Methods and results: Rats are randomly assigned to a DHA-rich or a control chow diet while drinking water or high fructose solution, followed by profiling of metabolic and cognitive phenotypes and the transcriptome and DNA methylome of the hypothalamus and hippocampus. DHA reduces se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…8 Numerous studies on lipidomics and neurological disorders have confirmed that lipid metabolism played an important role in brain lesions and mood disorders. 9,10 And peripheral metabolism changes can significantly affect the function of the brain. 9 Because of the important role of lipid metabolism in SLE and mood disorders, we considered the study of lipid metabolism in NPSLE mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Numerous studies on lipidomics and neurological disorders have confirmed that lipid metabolism played an important role in brain lesions and mood disorders. 9,10 And peripheral metabolism changes can significantly affect the function of the brain. 9 Because of the important role of lipid metabolism in SLE and mood disorders, we considered the study of lipid metabolism in NPSLE mice.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 And peripheral metabolism changes can significantly affect the function of the brain. 9 Because of the important role of lipid metabolism in SLE and mood disorders, we considered the study of lipid metabolism in NPSLE mice.…”
Section: Introductionmentioning
confidence: 99%